Waste Water Reduction Using Four Densities of Seaweed to Improve Water Quality for White Leg Shrimp (Litopenaeus white leg) Culture: Laboratory Scale - Samadan, Gamal M.; Syazili, Aras; Supyan, Supyan; Findra, Muhammad Nur (Aceh Journal of Animal Science, 2024)
The low environmental quality of pond water is caused, among other things, by the large amount of organic waste and nutrients (feed components) in pond water outflow. The remaining feed and feces (feces) decompose in pond water before being dumped into the nearby rivers, resulting in the discharge of high levels of nutrients and organic waste. One method for enhancing the effluent quality from aquaculture is a biofilter. In order to reduce and absorb dissolved organic contaminants, biofilters are used. It is possible to employ Gracilaria sp. as a biofilter, which is an efficient technique to increase sanitation. The study' goals were to determine how well Gracilaria sp. developed and how well seaweed absorbed N and P elements from vaname shrimp culture waste, specifically ammonia (NH3), nitrite (NO2), and nitrate (NO3). Three different treatments for the weights of the seaweed were employed in the study: 50, 75, and 100 grams. The analysis showed that the 100 g of Gracilaria sp. was very effective in absorbing N and P waste. It was discovered that N and P component absorption was, respectively, 75.10% and 75.15% effective.